REINTERPRETATION OF THE CIRCLE OF LIFE OF KARO PEMENA SOCIETY - Amelia Sebayang, Vanesia; Surbakti, Asmyta (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
This article discusses about the rites process undertaken by the Karo Pemena community in living the cycle of life from birth to death. Also examines the moral values that influence the cosmic order and the socio-cultural environment of a harmonious, pre-colonial society. This article uses the post-colonial perspective by Said. The study of postcolonialism was used to dismantle the dominance of Western thought in assessing the Eastern culture. The method used in this article is a method of hermeneutics to learn and find the meaning contained in the object of research in form of the phenomenon of human life, through understanding and interpretation. The purpose of this method is to open the essential and philosophical meaning derived from the symbols of the community of Karo Pemena. This article concludes the existence of the religion of Pemena began to decline in the political domination of the Dutch colonial government in Tanah Karo. The zending politics of Dutch has ruined the Karo Pemena until finally leaving the religion and affecting their socio-cultural system. Through the process of meaning, philosophical values in the cycle of life stages can be applied in Karo society according to the spirit of ethnic identity in post-colonial studies.